Study on vegetation flow along Kinta River by using LABSWEâ¢ - Shafiai, S.H. (Elsevier B.V., 2020)
Turbidity is considered a classical problem in Malaysian rivers. The level of turbidity is dependent on the amount of sediments and biological matter contained in the water. Therefore, this study proposes an approach to turbidity mitigation that involves simulating the effect of density and diameter of vegetation on water flow. This paper presents the numerical modelling of vegetation effect on water flow using Lattice Boltzmann Method for Shallow Water Equations (LABSWEâ¢) integrated with Rigid Vegetation Modelling (RVM). The proposed model was implemented on the Kinta River in Perak state, Malaysia as a case study. The simulation results show the effect of density and diameter of vegetation on water flow velocity. The optimum vegetation density and vegetation diameter values for river water turbidity reduction were found to be 0.05 and 0.005, respectively. Â© 2020 Faculty of Engineering, Alexandria University